Mathematical Simulation of Lost Circulation in Fracture and Its Control - Xiao Cai; Boyun Guo; Qingfeng Guo; Hongwei Jiang (Geofluids)
Lost circulation has been one of the major problems that impede efficient and cost-saving drilling operations. The nature of lost circulation and its control is not yet fully understood. A method to characterize the mud loss in fracture and the plugging process of lost circulation materials is highly desired to obtain a thorough understanding of mud losses in fracture and provide reference for lost circulation control. This paper presents an easy-to-use method to identify types of lost circulation in fracture and the corresponding control. Three analytical models are presented based on three loss mechanisms, namely, seepage/filtration in a fracture, pipe flow in a fracture, and gravity displacement in a fracture. A numerical model is developed to simulate the deposition of lost circulation materials in fractures and predict the time and the volume of drilling fluid needed for lost circulation control. Case studies with these analytical models provide a deeper insight of this subject. Sensitivity analyses with the numerical model identify the major factors responsible for lost circulation control. High viscosity of drilling fluid may prevent lost circulation, while low viscosity is desired for a fast control of lost circulation. Lowering the density of drilling fluid is another way to prevent the lost circulation and facilitate the deposition of lost circulation materials. Lost circulation materials with high density could deposit faster close to the wellbore and therefore accelerating the control process. High concentration of lost circulation materials is likely to shorten the plugging time, which should be determined referring to the severity of loss. This work provides drilling engineers a practical method for simulating the lost circulation and selecting lost circulation material.